Transformative F&I-Politik am Beispiel neuer Technologien in der Landwirtschaft und sozialer Innovationen - Irene Bertschek; Guido Bünstorf; Uwe Cantner; Carolin Häussler; Tilman Requate; Friederike Welter; Erich Arndt; Lukas Dreier; Daniel Erdsiek; Markus Rieger-Fels; Helge Dauchert; Lea Eilers; et al. (Wirtschaftsdienst, 2024)
– The transformation of economy and society requires far-reaching technological and social innovations. To utilise the economic opportunities of transformation and to mitigate the negative effects of structural change, a determined transformation-oriented R&I policy is needed. Using the example of new technologies in agriculture, it is shown how innovations can support the transformation towards greater sustainability. Furthermore, we analyse the role of social innovations as a cross-sectional instrument in managing the transformation and how policy makers can promote them.
Keywords: O13; O32; O35; O38; 330; Landwirtschaft; Sozialwirtschaft; Innovation; Deutschland; EU-Staaten; Landwirtschaft; Sozialwirtschaft; Innovation; Deutschland; EU-Staaten